Exploring Value‐Based Management Sophistication: The Role of Potential Economic Benefits and Institutional Influence1. (4th December 2018) - Firk, Sebastian; Schmidt, Torben; Wolff, Michael
ABSTRACT: The complexity of value‐based management (VBM) is often not captured in empirical research. In particular, potential differences in the extent of VBM implementation are not considered. Firms are predominantly classified dichotomously into either VBM "adopters" or "non‐adopters." In this study, we aim to fill this gap by introducing a framework to assess differences in the extent of VBM implementation (VBM‐sophistication) based on publicly available data. This approach enables us to study determinants of VBM‐sophistication based on a hand‐collected data set comprising 2, 683 firm‐year observations from 16 European countries between 2005 and 2014. Specifically, we investigate (i) whether potential economic benefits associated with VBM implementation lead to a higher level of VBM‐sophistication, and (ii) if this relation is influenced by extra‐organizational institutions (e.g., industry norms). Our results indicate that companies exhibit higher VBM‐sophistication if certain firm characteristics that increase the potential economic benefits of VBM are present. Moreover, our study provides evidence that this effect is enhanced by extra‐organizational institutions that pressure and support firms in realizing the potential benefits of higher VBM‐sophistication.